2019
DOI: 10.7759/cureus.5957
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Salivary Parameters and Oral Health Status Among Asthmatic and Nonasthmatic Adult Patients Visiting a Tertiary Care Hospital

Abstract: Introduction: Asthma is a chronic inflammatory disorder of the airways characterized by attacks of bronchoconstriction causing shortness of breath, coughing, and rapid breathing. Patients undergoing inhalation therapy are subjected to a higher risk of dental caries due to the reduced saliva secretion, decreased pH value, increased number of cariogenic bacteria caused by inappropriate oral hygiene, and the use of inhaling medicaments with dry powder.Methods: The descriptive study was carried out among 200 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…It is developed at all ages, in all genders, races and socioeconomic groups. Oral hygiene and quality of saliva also contribute to caries development [6]. Although dental science has made significant progress in recent decades, caries remain a popular health issue around the world.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is developed at all ages, in all genders, races and socioeconomic groups. Oral hygiene and quality of saliva also contribute to caries development [6]. Although dental science has made significant progress in recent decades, caries remain a popular health issue around the world.…”
Section: Discussionmentioning
confidence: 99%
“…Principal variables of saliva's quality that are associated with caries usually include the aciduric/acidogenic bacteria and rates of acid generation. In this sense, variables affecting caries development are, first, the quantity of saliva released in a selected time and, secondly, its acidneutralizing capacity [6,7,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that the use of inhalers in asthmatic patients decreases salivary flow and salivary composition, which in turn reduces the buffering effect of saliva that protects tooth structures from erosion. [70][71][72] In this regard, the medications used to treat asthma, which include inhaled Beta2 agonists and inhaled steroids, may play a role in these salivary changes. For example, Beta2 agonists have been shown to impair saliva production 73 and lower esophageal sphincter function, which leads to gastroesophageal reflux.…”
Section: Identifying Factors That Contribute To Dentin Hypersensitivitymentioning
confidence: 99%